2005
DOI: 10.1016/j.cardiores.2005.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases and atrial remodeling in patients with mitral valve disease and atrial fibrillation

Abstract: Concordant changes between MMP-expression and fibrosis during mitral valve disease, both in LA and RA, suggest involvement of MMPs in structural atrial remodeling. AF itself did not contribute to altered fibrosis or MMP-expression in the LA. The association between AF and RA changes may be precipitated by greater hemodynamic load due to tricuspid regurgitation in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
111
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(130 citation statements)
references
References 36 publications
9
111
0
10
Order By: Relevance
“…72 Studies have described how premature firing from the PVs can initiate AF by interacting with tissue mechanisms, using diffusion tensor imaging (at present, in vitro ). 73,74 These findings have been reproduced by cardiac magnetic resonance imaging (MRI), highlighting the very variable individual pattern of fiber orientation. 75 Future in vivo implementation (in addition to identification of fibrosis), combined with simultaneous mapping techniques, could allow individual tailoring of interruption of potential reentrant “pathways.” 76,77 …”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 89%
See 1 more Smart Citation
“…72 Studies have described how premature firing from the PVs can initiate AF by interacting with tissue mechanisms, using diffusion tensor imaging (at present, in vitro ). 73,74 These findings have been reproduced by cardiac magnetic resonance imaging (MRI), highlighting the very variable individual pattern of fiber orientation. 75 Future in vivo implementation (in addition to identification of fibrosis), combined with simultaneous mapping techniques, could allow individual tailoring of interruption of potential reentrant “pathways.” 76,77 …”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 89%
“…134,136 Some morphological studies have shown that fibrosis in humans is related to the underlying disease rather than being caused by AF. 73,137,138 The specific role of age and AF risk factors in atrial fibrosis was questioned by an autopsy study, in which only small amounts of fibrofatty tissue were described in atrial specimens from patients with a high mean CHA 2 DS 2 -VASc score of 4.3 but no AF. 139 In addition, a low correlation between risk factors and the fibrotic substrate as estimated from electroanatomic voltage mapping in patients with non-PAF has been described.…”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 99%
“…2). Charakterystycznymi cechami tego procesu są aktywacja fibroblastów, zwiększone odkładanie się tkanki łącznej oraz włóknienie [78][79][80]. U pacjentów z AF i towarzyszącymi stanami sprzyjającymi AF stwierdza się również nacieczenie przedsionków tkanką tłuszczową, nacieki zapalne, przerost miocytów, martwicę oraz amyloidozę [81][82][83][84].…”
Section: Przebudowa Przedsionków a Czynność Kanałów Jonowychunclassified
“…Przebudowa strukturalna wywołuje rozkojarzenie elektryczne między pęczkami włókien mięśniowych i miejscową niejednorodność przewodzenia [85], co sprzyja pobudzeniom nawrotnym (re-entry) i podtrzymaniu arytmii [86]. U wielu pacjentów ten proces przebudowy strukturalnej następuje przed wystąpieniem AF [78]. Ponieważ część tej przebudowy strukturalnej jest nieodwracalna, pożądane wydaje się wczesne rozpoczynanie leczenia [87].…”
Section: Przebudowa Przedsionków a Czynność Kanałów Jonowychunclassified
“…Factors associated with these structural changes include direct myocardial effects (pathognomonic inflammatory Ashoff bodies), ultrastructural changes, atrial fibrosis, immunoactive cytokines, and matrix metalloproteinase remodelling (decreased MMP-1 and MMP-3). [215][216][217] Reverse atrial remodelling (an immediate reduction in LA pressure and volume and an improvement in biatrial voltage; and further increases in RA voltage 6 months later) was demonstrated in 21 patients with isolated MS undergoing commissurotomy. 218 In contrast, atrial remodelling did not reverse in patients with lone AF undergoing successful AF ablation; indeed, substrate abnormalities progressed (decreased voltage and increased regional refractoriness) over the subsequent 6 -14 months.…”
Section: Atrial Cardiomyopathy Due To Valvular Heart Diseasementioning
confidence: 99%